Active suspension control: Performance comparison using proportional integral sliding mode and linear quadratic regulator methods - Md. Sam, Yahaya; Osman, Johari Halim Shah; A. Ghani, Mohd. Ruddin (2003)
The purpose of this paper is to compare the performance of the active suspension system using two different control strategies. The first strategy utilized the proportional integral sliding mode control scheme and the second one using the linear quadratic regulator method. A quarter-car model is used in the study and the performance of the controller is compared to the linear quadratic regulator and with the existing passive suspension system. A simulation study is performed to prove the effectiveness and robustness of the control approach.